PENGARUH KANDUNGAN BIOLOGICAL OXYGEN DEMAND AIR LIMBAH PENGOLAHAN KELAPA SAWIT TERHADAP KANDUNGAN UNSUR HARA NPK TANAH DAN PERTUMBUHAN TANAMAN JAGUNG - Riduansyah, Riduansyah; Junaidi, Junaidi; Widiarso, Bambang; Kurnia, Kurnia; Maulidi, Maulidi (Fakultas Pertanian, Universitas Janabadra, 2024)
The research aims to determine (1) the relationship between Biological Oxygen Demand (BOD) content and the nutrient content of anaerobic and aerobic pond wastewater; (2) the level of efficiency of inorganic fertilizer with the utilization of liquid waste at several waste water BOD levels; (3) the effect of providing liquid palm oil waste on the growth and yield of corn plants; (4) corn growth and yield at several wastewater BOD levels. The research was conducted at the experimental garden of the Faculty of Agriculture, Tanjungpura University. Soil analysis was carried out at the Soil Chemistry and Fertility Laboratory and wastewater BOD analysis was carried out at the Soil Health Laboratory, Department of Soil Science, Faculty of Agriculture, Tanjungpura University. The research used experimental methods with a Completely Randomized Factorial Design with treatments: 0 NPK, 2.25-0.75-040 NPK, and 4.5-1.5-0.75 NPK as well as giving Palm Oil Mill Effluent (POME) 100, 75, 50, and 25% BOD of anaerobic and aerobic wastewater ponds, so that 24 treatments were obtained, with 3 repetitions, 72 polybags. The waste water dose of 9 l per polybag is poured 3 l each per polybag in the morning, afternoon and evening. Variables observed: plant height, stem diameter, and number of leaves. Research results: giving POME to anaerobic and aerobic ponds until the 5th week did not have a real effect on height, stem diameter and number of corn leaves, but giving fertilizer until the 5th week had a real effect. Based on the Least Significant Difference Test (LSD) results, the best treatment is the L3N2 treatment (25% Liquid Palm Oil Waste and 9 g Urea, 7.50 g Sp-36, 5.6 g KCl). Keywords: corn; npk fertilizer; palm oil wastewater INTISARIPenelitian bertujuan untuk mengetahui (1) hubungan kandungan Biological Oxygen Demand (BOD) dengan kandungan hara air limbah kolam anaerobikdan aerobik; (2) tingkat efisiensi pupuk anorganik dengan pemanfaatan limbah cair pada beberapa level BOD air limbah; (3) pengaruh pemberian limbah cair kelapa sawit (LCKS) terhadap pertumbuhan dan hasil tanaman jagung; (4) pertumbuhan dan hasil jagung pada beberapa level BOD air limbah. Penelitian dilakukan di kebun percobaan Fakultas Pertanian Universitas Tanjungpura. Analisis tanah dilaksanakan di Laboratorium Kimia dan Kesuburan Tanah serta analisis BOD air limbah dilaksanakan di Laboratorium Kesehatan Tanah Jurusan Ilmu Tanah, Fakultas Pertanian, Universitas Tanjungpura. Peneltian menggunakan metode eksperimen dengan Rancangan Acak Lengkap Faktorial dengan perlakuan: 0 NPK, 2,25-0,75-040 NPK, dan 4,5-1,5-0,75 NPK serta pemberian Palm Oil Mill Effluent (POME) 100, 75, 50, dan 25 % BOD kolam air limbah anaerob dan aerob, sehingga diperoleh 24 perlakuan, dengan ulangan 3 kali ,72 polybag. Dosis air limbah 9 l per polybag disiramkan masing-masing 3 l per polybag pagi, siang dan sore. Variabel yang diamati: tinggi tanaman, diameter batang, dan jumlah daun. Hasil penelitian: pemberian POME kolam anaerobik maupun aerobik sampai pada mingu ke 5 tidak memberikan pengaruh nyata pada tinggi, diameter batang, dan jumlah helaian daun jagung, namun pemberian pupuk sampai minggu ke 5 memberikan pengaruh nyata. Berdasarkan hasil uji BNT perlakuan terbaik adalah perlakuan L3N2 (Limbah Cair Kelapa Sawit (LCKS) 25% dan 9 g Urea, 7,50 g SP-36, 5,6 g KCl). Kata kunci: air limbah kelapa sawit; jagung; pupuk npk